2003
DOI: 10.1016/s1015-9584(09)60216-5
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Triple Early Cancers Occurring in the Stomach, Colon and Gallbladder

Abstract: We report an unusual case of synchronous triple early cancers of the stomach, gallbladder and sigmoid colon. The patient was a 70-year-old man. Gastrointestinal endoscopy at a medical check-up initially revealed early gastric cancer. A thorough preoperative investigation showed a gallbladder tumour and early colon cancer. Endoscopic mucosal resection was performed for the colon cancer. Microscopically, the specimen showed well-differentiated adenocarcinoma involving the submucosal layer. Distal partial gastrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…In the literature, only five cases were related worldwide since 2005 [1] . However, in the last years, multiple primary tumors have been more frequently documented due to the increase in life expectancy and the improvement of diagnosis techniques [1,7] . A Japanese study done by Horii et al evidenced that microsatellite instabilities were frequently observed in multiple primary neoplasms rather than in single neoplasms [2,8] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, only five cases were related worldwide since 2005 [1] . However, in the last years, multiple primary tumors have been more frequently documented due to the increase in life expectancy and the improvement of diagnosis techniques [1,7] . A Japanese study done by Horii et al evidenced that microsatellite instabilities were frequently observed in multiple primary neoplasms rather than in single neoplasms [2,8] .…”
Section: Discussionmentioning
confidence: 99%
“…The Warren and Gates criteria define synchronic tumors and can be applied if a second primary tumor falls into these criteria: (a) each tumor should represent a single form of malignancy; (b) each tumor has to be distinct from each other; and/or (c) the metastatic tumor should be excluded [1,7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tumor type, location, stage and progression, as well as the patient's general health status should be considered. The treatment of choice involves curative surgical resection of each cancer, followed by radiotherapy and chemotherapy (16)(17)(18). The prognosis should be determined independently as a function of the tumor stage and treatment results for each cancer.…”
Section: Discussionmentioning
confidence: 99%